Economics Analysis of Differences in Tax Aggressiveness Before and After Tax Amnesty and Influencing Factors - Natajaya Santana; Darmanto Darmanto; Ari Warokka (Jurnal Pendidikan Ekonomi, 2024)
Tax amnesty public policy is an effort by the Government to collect tax revenues, and at the same time it is expected to be able to make taxpayers compliant. This research is quantitative research with an exploratory approach. This study uses secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) during the period 2011 to 2022. The research sample consisted of 144 companies that had met the criteria. The data were analyzed using the SEM-PLS method with the help of WarpPLS 8.0 software. The results show that tax amnesty public policy intervention makes a difference in the amount of corporate tax aggressiveness although statistically insignificant. Tax rates have a significant effect on the amount of tax aggressiveness both before and after the implementation of the tax amnesty while tax complexity, political connection, company age, company size and leverage have insignificant effect. The findings provide implications for the study of micro and macroeconomics. Keywords: tax amnesty, tax aggressiveness, tax rate, economics learning